Comparison of the Turkish versions of the Glasgow coma scale and four score used by intensive care nurses for neurological evaluation. Issue 9 (15th August 2021) - Özçelik, Emine Ezgi; Celik, Selda
Abstract: Objective: This study aimed to compare the use of the Turkish versions of the Glasgow Coma Scale (GCS) and Full Outline of UnResponsiveness (FOUR) Score by intensive care nurses in neurological evaluation. Materials and Methods: This cross‐sectional study was conducted between July 2018 and March 2019 with 92 patients in the general intensive care unit (ICU) of the training and research hospital of a private university. Data were collected using nurse and patient information forms, the GCS and the FOUR Score. The patients were evaluated by 27 intensive care nurses. To evaluate interrater reliability of the GCS and FOUR Score, each patient in the study was evaluated using both scales by two nurses who were blinded to each other's responses. Results: Comparison of the patients' mean GCS and FOUR Score values from the two nurses revealed no significant difference in subscale or total scores ( p  > 0.05). Evaluation of interrater reliability demonstrated very good agreement ( κ  = 0.935, p  < 0.001). There was also very good agreement between the results of the two nurse groups when the patients' total scores were categorised according to the cut‐off points for the two instruments ( κ  = 0.927, p  < 0.001). Conclusion: This study demonstrated excellent agreement in the Turkish GCS and FOUR Score values, indicating that both scales can be used in neurological evaluation. Both instruments are reliable and easily applied by ICU nurses. Relevance to Clinical Practice: The Turkish versions of the FOUR Score and GCS are both appropriate for use in intensive care units and are reliable tools for use by intensive care unit nurses.